The Impact of Reclamation of the Central Point of Indonesia (CPI) Area in Makassar City on the Socioeconomic Conditions of the Community - Indra Syamsuddin; Uca Sideng; Ibrahim Abbas; Sulaiman Zhiddiq; Amal Arfan (LaGeografia, 2022)
This study aims to determine whether the construction of the Center Point Of Indonesia (CPI) affects the socio-economic conditions of the people in the Makassar City sub-district. The independent variable in this study is the construction of the Center Point Of Indonesia (CPI) while the dependent variable is the socio-economic condition of the community. The population in this study is the people of Mariso District, while the sample is 100 people. The type of research used is descriptive quantitative. The sampling technique used is random sampling. The instrument used is a questionnaire with a Likert scale. The results showed that the positive impact of the Center Point Of Indonesia (CPI) development was the availability of employment and many available facilities and infrastructure, while the negative impact was the reduced income of the community, especially fishermen who were looking for catch around the Center Point Of Indonesia (CPI) construction site.